HUBUNGAN STIMULASI BERMAIN, KUALITAS INTERAKSI DAN VERBAL ABUSE DENGAN PERKEMBANGAN PERSONAL SOSIAL ANAK USIA PRASEKOLAH - Ulva Noviana (NHM PRESS, 2019)
One aspect of development in preschoolers is personal social development. Preliminary study results conducted on 10 children obtained results 6 children with caution assessment, 2 children with delayed assessment, and 2 children with normal assessment with the Suspect interpretation on the assessment of the Denver II test.The purpose of this study was to determine the relationship of play stimulation, the quality of interaction, and verbal abuse with the social development of preschoolers in kindergarten of Al-Djufri VI. This research use Analytical method with Cross Sectional approach with independent variables is play stimulation, interaction quality, and verbal abuse and the dependent variable is personal social development. The population is the parents of preschool children in kindergarten of Al-Djufri VI as many as 38 people with a total sample of 38 people Using total sampling technique. The instruments in this study used questionnaires on independent variables and used the Denver II test on the dependent variable.Statistical test using spearman rank test with significance level of 0.05. The result of this study using spearmen rank shows there is relationship of play stimulation with social development of preschool children with p value 0,000 <0,05 and r = 0,677, There is relationship of interaction quality with social development of preschool age children with p value 0,000 <0,05 and r = 0,724, There is relationship of verbal abuse with social development of preschool age children with p value 0,040 <0,05 and r = 0,334. Play stimulation, interaction quality, and verbal abuse have a relationship with personal social development. Parents and teachers are advised to be able to increase their knowledge as an effort to prevent child development delay in social aspect by doing screening test on health service to measure child development level.